Inventory of Science Verses in Islamic Religious Education Learning - Zulaiha, Eni; Srifatonah, Pebrianu (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2025)
Integrating Islamic religious teachings and modern science in the Islamic Religious Education (PAI) curriculum is an important challenge in holistic basic education. This study examines the process of inventorying Qur'anic verses integrated with scientific concepts in Islamic Education learning books at Manaaratul Iman Elementary School. Using a qualitative approach through document analysis and Seyyed Hossein Nasr's hermeneutic framework, this study found that identifying, selecting, and interpreting verses was not fully systematic and still lacked the application of thematic (maudhu’i) methods. The lack of teacher involvement and contextual information, such as asbabun nuzul, also weakens the integration between science and religion. The findings fill the void of practical studies integrating science and religion at the basic education level. This research analyzes the curriculum process by concretely integrating the Qur'an and science. Through periodic evaluations, the involvement of tafsir experts and scientists to apply the maudhu’i method systematically, and teacher training in thematic methods are also important recommendations so that the integration of religion and science does not stop at the concept level, but becomes a transformative Islamic curriculum model that is relevant to the times.